Ethical Entrepreneurship and Fair Trade - Wempe, Johan (Journal of business ethics, 2005)
Due to several recent scandals, Business Ethics is now firmly embraced. Whereas in the 1980s and early 1990s there were serious doubts expressed about combining ethics and business, the link now seems to have become self-evident. Fundamental questions about the tensions between business and ethics however continue to receive little attention. In this paper, based upon a debate concerning the Fair Trade company, the strains between business and ethics are analyzed. The article shows how several great thinkers have already considered this tension. Three ways to conceptualize the tension between business and ethics have been distinguished, and these are outlined in the paper. In one approach, ethical entrepreneurship, value tensions are perceived as a source for entrepreneurship. However, this approach presupposes pluralistic ethics. Thinking only in terms of black and white is seen as blocking the ability to adequately handle the tension between business and ethics. Opting for ‘‘ethical entrepreneurship’’, as by Fair Trade, has fundamental and important consequences for the company’s communication policy.